Amsal 12:18 sebagai Landasan Teologis dalam Merespons Fenomena Ujaran Kebencian di Ruang Digital - Sapto Harsoyo; Suparman Partoredjo; Saefnat Saetban; Setya Hari Purnomo (SERVITA DEI : Jurnal Teologi dan Pendidikan Kristen, 2025)
The phenomenon of hate speech in the digital sphere has become one of the most serious challenges in the context of modern social and religious life. This study aims to analyze Proverbs 12:18 as a theological foundation for responding to the dynamics of hate speech, in order to propose principles of digital communication ethics rooted in biblical wisdom. This research employs a qualitative method with hermeneutical approach to the text of Proverbs 12:18 to explore its theological and ethical dimensions for restorative communication practices. The findings reveal that Proverbs 12:18 emphasizes three core principles: the principle of power and integrity in speech, the principle of wisdom as an ethical framework for communication, and the principle of speech as a means of relational restoration. This study offers both theological and practical contributions in shaping digital communication ethics that are relevant to the contemporary church and society.